New Forms of Electrospun Nanofibers Applied in Cardiovascular Field - Huang, Weimin; Huo, Mengen; Cheng, Nan; Wang, Rong (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular disease (CVD) is one of the leading causes of death worldwide. Graft strategies and Stem cell therapy are growing rapidly. However, the relatively poor survival rate of stem cells in the ischemic heart as well as the low long-term patency rate of the transplanted vessels, are the main challenges currently faced. In recent years, the rapid development of electrospinning technology provides a new direction for it. Unlike previous reviews, this research enumerates the experimental methods and applications of electrospinning technology combined with nanofibrous materials in myocardial infarction, heart valves, cardiac patches, artificial blood vessels, cardiovascular surgeries and human cardiovascular health monitoring from the perspective of cardiovascular surgery. In the end, this review also summarizes the limitations, unresolved technical challenges, and possible future directions of this technology for cardiovascular disease applications.